2001
DOI: 10.4049/jimmunol.166.12.7579
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Antigen-Specific CD8+ T Cells Are Encephalitogenic and Produce Severe Disease in C57BL/6 Mice

Abstract: Encephalitogenic T cells that mediate experimental autoimmune encephalomyelitis (EAE) are commonly assumed to be exclusively CD4+, but formal proof is still lacking. In this study, we report that synthetic peptides 35–55 from myelin oligodendrocyte glycoprotein (pMOG35–55) consistently activate a high proportion of CD8+ αβTCR+ T cells that are encephalitogenic in C57BL/6 (B6) mice. The encephalitogenic potential of CD8+ MOG-specific T cells was established by adoptive transfer of CD8-enriched MOG-specific T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
293
5
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 397 publications
(315 citation statements)
references
References 50 publications
9
293
5
8
Order By: Relevance
“…Autoreactive CD8 ϩ T cells have also been implicated as potent effector cells in several animal models of autoimmune diseases including EAE. Adoptive transfer studies of CD8 ϩ T cells isolated from animals with EAE have successfully propagated the disease to naïve recipients (24,25). Mixed results have been reported in EAE studies in animals lacking CD8 ϩ T cells.…”
mentioning
confidence: 75%
“…Autoreactive CD8 ϩ T cells have also been implicated as potent effector cells in several animal models of autoimmune diseases including EAE. Adoptive transfer studies of CD8 ϩ T cells isolated from animals with EAE have successfully propagated the disease to naïve recipients (24,25). Mixed results have been reported in EAE studies in animals lacking CD8 ϩ T cells.…”
mentioning
confidence: 75%
“…Huseby et al have demonstrated that adoptive transfer of H-2K k -restricted CD8 T cells specific for MBP [79][80][81][82][83][84][85][86][87] induces clinical experimental autoimmune encephalomyelitis (EAE) in C3H mice, reproducing features of MS lesions usually not observed in CD4 T cell-driven EAE [56]. Furthermore, adoptive transfer of MOG specific CD8 T cells induces progressive EAE in C57BL/6 mice, independent of CD4 T cells [57]. The adoptive transfer of H-2D b -restricted CD8 T cells specific for the short MOG 37-46 peptide also induces EAE into C57Bl/6 recipients [58].…”
Section: Cd8 T Cells In Animal Models Of Msmentioning
confidence: 99%
“…Chronic relapsing or nonrelapsing forms of EAE can be induced in rodents by active immunization with myelin Ags such as myelin oligodendrocyte glycoprotein (MOG) (1) or by passive transfer of MOGspecific CD4 ϩ or CD8 ϩ T cells and anti-MOG Abs (2,3). The pathology of EAE is well described, differs between models, but is generally characterized by increased permeability of the bloodbrain barrier, perivascular inflammatory infiltrates comprised of T cells, B cells, macrophages, and granulocytes, and demyelination leading to an ascending paralysis of the extremities.…”
Section: E Xperimental Autoimmune Encephalomyelitis (Eae)mentioning
confidence: 99%